Comparative Benefit of Evening Primrose Oil and Soybean Oil on Treatment Satisfaction and Quality of Life among Postmenopausal Women - raghad mohammed; Manal Khalid Abdulridha; Bushrah Abd Al-Jbori (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2024)
Background: Medicinal herbs as alternative therapies, commonly used to treat menopausal symptoms, and some studies have shown that they can be useful in treating menopausal syndrome, which have been linked to worse self-rated health, and decreased work productivity.